(untitled) (Precision Medicine Communications, 2023)
In this issue, Shah and colleagues reviewed and discussed the pharmacogenetics of tacrolimus in solid organ transplant patients, Ullah and colleagues performed a meta-analysis on the association of GABRG2 rs211037 gene polymorphism with epilepsies and pharmacoresistance to anti-epileptic drugs, Mansoor and colleagues carried out an integrative investigation for the prioritization of candidate genes and unveiled their interaction with celecoxib for targeted therapeutic applications, Nimra and Robab reviewed the pharmacogenomics of Leukemia for unlocking personalized treatment strategies, Hussain and colleagues investigated the association of GATM gene polymorphism with statin-induced myopathy.